29 Open-pilot of an ed-based multi-session remote therapy intervention (rti) for violence. (19th September 2017) - Carter, Patrick; Roche, Jessica; Walton, Maureen; Cunningham, Rebecca
Abstract : Statement-of-Purpose: Violence is a leading cause of death for urban youth. This pilot evaluated the feasibility of a remote therapy intervention (RTI) for violence and substance use among drug-using youth seeking Emergency Department (ED) care for assault. Methods: Youth (age:14–24) with assault-injury were approached in the ED; those screening positive for past 6 month drug use were enrolled in an open pilot. The 8-session RTI combined elements of motivational interviewing and cognitive behavioural therapy for substance use/violence (e.g., refusal skills, conflict resolution, anger management), and strengths-based care management to link youth with community resources. The RTI was delivered in-person by a therapist during the ED visit ( 35 min) and remotely (e.g., phone) in the 12 weeks following the visit. Computerised assessments were completed at baseline, weekly prior to sessions, and at a 4 month follow-up. Results were analysed descriptively and with paired tests (baseline, follow-up). Results: 20-youth were enrolled in the pilot [M age=21; 55% female; 60% African-American; 70% public assistance; 90% past 2 month marijuana use]. The RTI was acceptable and feasible, with 91% enrollment of eligible youth, 100% of enrolled youth completing the in-person ED session, 70% completing 5 remote sessions, and >80% completing the 4 month follow-up. Participants rated sessions highly, with 80% reporting that it was very/extremely helpful to have post-ED phone sessions. Paired comparisons demonstrated a decrease in violence (aggression/victimisation) prevalence (90%-vs.-20%;p<0.01), and non-significant decreases in drug use frequency (2.61.6-vs.-2.52.3), violence frequency (6.23.5-vs.-2.75.9), and the frequency of drug (9.97.1-vs.-7.97.1), and violence (2.32.2-vs.-0.91.3) consequences. Conclusion: A multi-session violence intervention delivered remotely is acceptable and feasible. Significance/Contribution: Effective individual- and community-based interventions are urgently needed to decrease youth violence. Based on our initial pilot, the RTI is a promising theory-based individual-level intervention for high-risk assault-injured ED youth. Further study is needed to determine intervention efficacy on violence outcomes (e.g., violent re-injury, arrests).